The Influence of Marketing Strategy on Marketing Performance from a Management Perspective in the Disruption Era - I Gusti Ngurah Satria Wijaya; Annisa Balqis Bashira Syahrir Malintang Latanro; Ni Nyoman Arie Rahayu Sugianitri (Bina Nusantara University, 2024)
The world continues to develop and change, and everything is digital-based in the current era of disruption. The retail industry is one of the business sectors most severely impacted by the COVID-19 pandemic and the disruption era. Numerous businesses or retail issuers also see a drop in sales and even suffer losses. The research aimed to evaluate the most successful marketing tactics toward marketing performance in the disruption era from a management perspective. The major data used came from questionnaires given to management with digitized or digital marketing. A total of 282 data were collected using the purposive sampling technique to determine the respondents in Denpasar City. Structural Equation Model (SEM) analysis was employed in this investigation. The research outcomes are strategies that effectively influence marketing performance in the disruption era, including marketing mix strategy, online affiliate marketing strategy, and social media strategy. The marketing mix strategy cannot be abandoned despite changes in the disruption era. There can only be a change in strategy using digital marketing media. The research novelty lies in its findings, which support the Resource-Based View (RBV) theory, the marketing tactic employed to enhance marketing effectiveness in the disruption era. The practical implications include policy recommendations for business management and marketing methods to improve marketing performance in the disruption era.